The Effectiveness of Implementing the Zero Waste School Program on Enhancing the Values of Cooperation and Student Participation at SMPN 1 Taliwang - Muis, Abdul; Suparman, Suparman; Junaidi, Junaidi (JUPE : Jurnal Pendidikan Mandala, 2023)
The school programs play a crucial role in shaping students' characters, including the spirit ofcooperation (gotong royong). The value of gotong royong is important to instill in students as it contributes to broader educational goals. This research aims to explain the implementation of the zero waste school program in enhancing students' spirit of cooperation and participation at SMPN 1 Taliwang. This study employs a descriptive method with a Mix Method Research (MMR) approach. The research will involve 7th and 8th-grade students, selected using purposive sampling. The research instrument utilized is a questionnaire to measure students' spirit of cooperation and participation. The findings of the research indicate that: 1) the implementation of the zero wasteschool program achieved an average score of 4.2, categorized as "Good"; 2) there was an increase in the spirit of cooperation, with an average score of 4.3, categorized as "very high"; 3) student participation received an average score of 4.5, indicating a generally very high level (close to the maximum score of 5.00); and 4) the supporting factors for implementing the zero waste school program at SMPN 1 Taliwang were reinforced by the “Clean Saturday Movement” school program. In conclusion, the implementation of the zero waste school program to enhance students' spirit of cooperation and participation at SMPN 1 Taliwang has been effective. It is recommended to continue and further develop the zero waste school program while involving all school stakeholders. This approach will ensure the program's sustainability and a lasting positive impact on students' character and participation.